Online video conferencing therapy and the person-centered approach in the context of a global pandemic. (2nd October 2021) - Rodgers, Brian; Tudor, Keith; Ashcroft, Anton
ABSTRACT: Working therapeutically online can offer a number of challenges, not least to therapists' ideas about ways of engaging and working with clients, and views of reality, as well as to familiar theories about therapy, including the therapeutic relationship or ways of therapeutic relating. Taking Rogers' theory of certain necessary and sufficient conditions – of psychotherapeutic change and of constructive personality change – this article considers each condition with regard to different experiences and aspects of online video conferencing therapy. In doing so, the article tests not only the necessity and sufficiency of these six conditions but also, and in keeping with Rogers' methodology, of the theory itself. As the article was written in a time of a global pandemic, it also offers reflections on the experiences of the authors working therapeutically online in this context.